Implementasi Pendidikan Inklusi dalam Membangun Mental Toleran Berbasis Pendidikan Agama Islam di Sekolah Dasar Negeri 06 Malang - Bakri, Maskuri (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2020)
The objectives of this research are to elaborate and analyze certain values, implementation processes, and inclusive education model in developing tolerant mentality based on Islamic education in the State Elementary School 06 Malang. This research uses case study of qualitative approach, purposive technique data selection, and snowballing technique for its data development. It uses observation, interview, and documentation study for its data gathering. Miles and Huberman analysis is conducted using internal and external data audits to assure data accuracy. Results of the research show that the inclusive education values include diversity which believes that humans are diverse and are having impartial, social, tolerance, and caring characteristics which foster their social sensitivity to genuinely support others in need. Inclusive education process for building tolerant mentality of Islamic education is comprised of learning, role modelling, affirmation, and habituation to build students’ tolerant mentality inside and outside classes. This embodied tolerant mentality is the awareness, acceptance, and respect toward diversity which can encourage collaboration among the student’s diversity to complement each other’s weaknesses and strengths. The implementation of inclusive education model is a combination of full-inclusive and partial-inclusive. Students are at the same class. However, in a specific condition the special-need students will be placed in a special class without reducing the right of regular students to learn. Likewise, the special-need students can learn based on their level of competencies